Influence of thiopheneyl‐based twisted backbone on the properties of α‐diimine nickel catalysts in ethylene polymerization. (10th August 2021) - Liao, Daohong; Behzadi, Shabnam; Hong, Changwen; Zou, Chen; Qasim, Muhammad; Chen, Min
Abstract: The modification of ligand sterics has become a prevalent strategy to tune the properties of α‐diimine‐type nickel catalysts. The majority of the works in this field focus on the modifications of the aniline moiety. In this contribution, we decide to explore the influence of backbone structures. Specifically, nickel complexes bearing 2, 5‐dimethyl‐thien‐3‐yl and 2‐methyl‐5‐phenylthien‐3‐yl backbone structures were prepared and characterized. In comparison with the nickel analogue with methyl backbone, these new nickel complexes demonstrate much higher catalytic activity and thermal stability upto 80°C in ethylene polymerization and generate polymer products with much higher molecular weight along with lower branching density and higher melting points. It is believed that the bulky substituents at ligand backbone will exert influence on the N ‐aryl moieties and increase steric bulkiness around the metal center. This backbone strategy is applicable for future studies in other catalytic reactions. Abstract : New α‐diimine‐type nickel complexes with novel 2, 5‐dimethyl‐thien‐3‐yl and 2‐methyl‐5‐phenylthien‐3‐yl backbone structure have been synthesized and characterized. The catalysts exhibit high activity and thermal stability and also provided high molecular weight polyethylene compared to classical methyl backbone containing analogous.